Hyponatremia in babies: a 11-year single-center study - Liu, Xu; Xie, Yanshu; Tang, Jing; Zhong, Jingzi; Lan, Dan (Frontiers in Pediatrics, 2024)
Introduction: Hyponatremia is one of the most prevalent water-electrolyte disturbances encountered in clinical practice in pediatrics and can arise from various conditions. However, there are limited reports on hyponatremia in hospitalized infants. The objective of this study was to provide an overview of the incidence, etiologies, and clinical characteristics of hyponatremia in hospitalized babies (from birth to 3 years old) at a tertiary hospital.Method: Computer records of all hospitalized babies (from birth to 3 years old) with hyponatremia were extracted from the First Affiliated Hospital of Guangxi Medical University's clinical databases.Results: 801 patients from 39,019 hospital admissions were found to have hyponatremia and the overall prevalence of this condition was 2.05% in babies. Patients with hyponatremia due to aldosterone signaling abnormalities, neurological disorders, and liver diseases exhibited more severe outcomes than those with other etiologies.Conclusions: Various conditions can result in hyponatremia in hospitalized babies. Aldosterone signaling abnormalities were not that uncommon and it could lead to severe hyponatremia in babies.